2020
DOI: 10.18632/aging.102662
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Fazekas scores from automatic segmentations of white matter signal abnormalities

Abstract: The Fazekas scale [1] is a widely used method to visually rate hyperintense white matter signal abnormalities (WMSA) in magnetic resonance imaging (MRI) data, both in clinical practice and research [1-4]. High Fazekas WMSA burden (i.e. confluent WMSA, Fazekas 2 or 3 scores) is associated with greater cognitive www.aging-us.com

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 30 publications
4
44
0
Order By: Relevance
“…Because multiple pathologies usually coexist in the brain of cognitively unimpaired individuals [62,63], future studies should thus unveil the pathologies underlying non-AD patterns of GM and WM neurodegeneration in SCD. Investigating pathologies such as cerebrovascular disease and tauopathies is warranted due to their contribution to SCD in community-based cohorts [60,63,11,64]. A limitation of our cohort is that we do not have biomarkers for amyloid-beta and tau-related pathologies.…”
Section: Limitationsmentioning
confidence: 99%
“…Because multiple pathologies usually coexist in the brain of cognitively unimpaired individuals [62,63], future studies should thus unveil the pathologies underlying non-AD patterns of GM and WM neurodegeneration in SCD. Investigating pathologies such as cerebrovascular disease and tauopathies is warranted due to their contribution to SCD in community-based cohorts [60,63,11,64]. A limitation of our cohort is that we do not have biomarkers for amyloid-beta and tau-related pathologies.…”
Section: Limitationsmentioning
confidence: 99%
“…Hence, in the KIDS cohort, WMSA were assessed through the Fazekas scale on FLAIR images. Importantly, hypointense WMSA from FreeSurfer and the Fazekas scale are strongly associated with each other [27]. We followed a previous study that demonstrated that hypointense WMSA from FreeSurfer and Fazekas scores can be combined together by converting hypointense WMSA into low and high CVD burden [27].…”
Section: Magnetic Resonance Imagingmentioning
confidence: 98%
“…Importantly, hypointense WMSA from FreeSurfer and the Fazekas scale are strongly associated with each other [27]. We followed a previous study that demonstrated that hypointense WMSA from FreeSurfer and Fazekas scores can be combined together by converting hypointense WMSA into low and high CVD burden [27]. Hence, we computed a unique WMSA variable by applying a cut-off of 0.00321 on hypointense WMSA from FreeSurfer after total intracranial volume (TIV) adjustment.…”
Section: Magnetic Resonance Imagingmentioning
confidence: 99%
See 2 more Smart Citations